2010
DOI: 10.1073/pnas.1007326107
|View full text |Cite
|
Sign up to set email alerts
|

β-Catenin activity in the dermal papilla of the hair follicle regulates pigment-type switching

Abstract: The switch between black and yellow pigment is mediated by the interaction between Melanocortin receptor 1 (Mc1r) and its antagonist Agouti, but the genetic and developmental mechanisms that modify this interaction to obtain different coat color in distinct environments are poorly understood. Here, the role of Wnt/β-catenin signaling in the regulation of pigment-type switching was studied. Loss and gain of function of β-catenin in the dermal papilla (DP) of the hair follicle results in yellow and black animals… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
51
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 60 publications
(55 citation statements)
references
References 34 publications
3
51
1
Order By: Relevance
“…Blocking the capacity of DP cells to respond to Wnt signals caused a change in the production per DP cell of secreted factors that act on adjacent keratinocytes to regulate hair morphogenesis and anagen re-entry (Enshell-Seijffers et al, 2010a;Enshell-Seijffers et al, 2010b) . In the work reported here, we reveal a different mechanism whereby changes in the number of DP cells specify changes in hair size, shape and cycling frequency.…”
Section: Research Article Development 140 (8)mentioning
confidence: 99%
See 1 more Smart Citation
“…Blocking the capacity of DP cells to respond to Wnt signals caused a change in the production per DP cell of secreted factors that act on adjacent keratinocytes to regulate hair morphogenesis and anagen re-entry (Enshell-Seijffers et al, 2010a;Enshell-Seijffers et al, 2010b) . In the work reported here, we reveal a different mechanism whereby changes in the number of DP cells specify changes in hair size, shape and cycling frequency.…”
Section: Research Article Development 140 (8)mentioning
confidence: 99%
“…The dermal papilla (DP) serves as a physical niche for these matrix progenitors (Legué and Nicolas, 2005) and provides signals that contribute to specifying the size, shape and pigmentation of the hair shaft (Enshell-Seijffers et al, 2010a;Enshell-Seijffers et al, 2008;Enshell-Seijffers et al, 2010b). At the end of the growth phase, these progenitors stop dividing and either differentiate or degenerate (supplementary material Fig.…”
Section: Introductionmentioning
confidence: 99%
“…BMP activity in the dermis has been suggested to be inhibitory to anagen induction, with suppression by the BMP antagonist, Noggin, showing a shortened refractory telogen phase and therefore earlier anagen induction (Plikus et al, 2008). However, it has been reported that increased β-catenin activity in the DP results in the upregulation of BMP signalling in the hair follicle bulb, which has been shown to be essential to the hair inductive properties of the DP, both in vitro and in vivo (Enshell-Seijffers et al, 2010b;Rendl et al, 2008). In vitro treatment of DP cells with BMP6 resulted in maintenance of the DP molecular signature and enhanced their ability to induce hair follicle formation in in vivo assays compared to untreated DP cells.…”
Section: The Dermal Papilla and Bulge Stem Cell Modulationmentioning
confidence: 99%
“…It has been suggested that Wnt/β-catenin signalling begins with the secretion of Wnt by matrix cells, which induces β-catenin production in the DP. Consequently, β-catenin signals follicular keratinocytes in the adjacent hair matrix to proliferate, thereby inducing hair follicle regeneration (Enshell-Seijffers et al, 2010b). Increased β-catenin activity in the DP results in the upregulation of FGFs, insulin-like growth factors (IGFs), Wnts and BMPs, all of which are implicated in the proliferation of hair follicle keratinocytes during anagen.…”
Section: The Dermal Papilla and Bulge Stem Cell Modulationmentioning
confidence: 99%
See 1 more Smart Citation